Pengaruh Penerapan Pendekatan Deep Learning Berbantuan Media Congklak Terhadap Hasil Belajar Siswa Kelas III Materi Perkalian Di SDN Kranjingan 03 - Susanto; A'izzatul Khumairoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In Indonesia, the mathematics learning process tends to apply abstract concepts, directing students to memorize rather than understand, and is considered a difficult and unpleasant subject. The lack of contextualization in learning often results in students being taught without the use of concrete media or media related to real-life experiences. One alternative that can be used is to apply a deep learning approach assisted by congklak media. This study aims to examine the significant effect of applying a deep learning approach assisted by congklak media on the learning outcomes of third-grade students in multiplication at SDN Kranjingan 03. This study used a pre-experimental pattern, namely a One Group Pretest-Posttest design. The subjects of this study were all third-grade students at SDN Kranjingan 03, consisting of 28 students. The data were analyzed using normality tests and pairedt samples tests. The results showed that there was a significant effect of the application of the deep learning approach assisted by the congklak media on the learning outcomes of third-grade students in multiplication at SDN Kranjingan 03. This was proven by the results of the hypothesis test using the Paired Samples Test, with the result that the t-count value was -11.811 with a t-table value at df = 27 with a significance level of 5% being 2.052. This shows that the t-count value is ≥ t-table. In addition, the significance value (sig. 2 tailed) reached 0.000 < 0.05. Thus, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted.